Impact of sexual violence on mental health of women: a qualitative systematic review - Artykbayeva, Akbota (Nazarbayev University School of Medicine, 2019)
Women who had ever assaulted sexually encounter mental health sequelae and are in a greater risk of developing variety of diagnoses, such as post-traumatic stress disorder and others. Mental health consequences closely related to characteristics of victims and assault, disclosures, help-seeking, and with the sociocultural factors in its broad meaning. Aim was to reveal different aspects in progress of spectrum of mental health disorders by thematic synthesis of qualitative literature on experiences of survivors and to reveal what are barriers to and facilitators of recovery.
Keywords: sexual violence